2016
DOI: 10.2217/fvl-2016-0089
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus PUL97 Drug-Resistance Mutations in Congenitally Neonates and HIV-infected, No-Drug-Treated Patients

Abstract: Aim: Human cytomegalovirus (HCMV) treatment is hard to achieve because of viral protein target sequence variations. Objectives: We aimed to find HCMV pUL97 kinase variations in HIV- and congenitally infected patients. Methods: Twenty HCMV-positive DNA samples from nonganciclovir treated congenitally infected neonates and HIV positive patients were used for PCR restriction fragment length polymorphism. Variations were assessed computationally for pUL97 functionality. Results: P521L, D605E and N597Y substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a parallel work, we investigated pUL97 polymorphism in both groups [20] and found that there are significantly more polymorphisms in pUL97 from congenitally infected neonates than from HIV-positive adults. It seems both immune system pressure and viral interactions may be involved in pUL27 sequence variation.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel work, we investigated pUL97 polymorphism in both groups [20] and found that there are significantly more polymorphisms in pUL97 from congenitally infected neonates than from HIV-positive adults. It seems both immune system pressure and viral interactions may be involved in pUL27 sequence variation.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid substitutions were analyzed for their potential to confer any anti-HBV drug resistance or functional impact on the structural configuration by Mutation Assessor server as described before [16].…”
Section: Evaluation Of Drug-resistance Conferring Substitutions and Hmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV), also known as human herpes virus-5, is a ubiquitous organism from the Herpesviridae family [1]. HCMV infection can affect multiple organs and is a main health concern in congenitally infected infants [2,3] and immunocompromised patients [4]. The infection is more prevalent among individuals at risk of human immunodeficiency virus (HIV) infection, drug abusers, and homosexual men infected with HIV [5].…”
Section: Introductionmentioning
confidence: 99%